Relevance of pin-on-disc and inertia dynamometer bench experiments for braking emission studies. (October 2019) - Philippe, F; Xiang, M; Bressot, C; Chen, Y; Guingand, F; Charles, P; Loigerot, J; Morgeneyer, M
Abstract: Over the last years, the task of reducing automobile pollution was focused on the car's engine. Now, the non-exhaust emission becomes a major contributor, and its control is the next objective to reach the zero-emission car. A major part of those non-exhaust emissions comes from brake wear, caused by the friction between the brake disc and pads. This emission is the result of complex tribological phenomena that has still to be determined. Nevertheless, this emission remains controllable and is the next lever for reducing car pollution. The problem of this field is the noncomparable results obtained by stakeholders due to their different measurement protocol. The first challenge is, thus, to define the best protocol in order to get a representative, reliable and repeatable measurement of particle emissions. The present article discusses a step of the selection process: which laboratory indoor method is the best for simulating the generation of braking particles? The pin-on-disc and the inertia dynamometer bench are the only two existing methods for braking simulation.